Prognostic value of transthoracic echocardiography and biomarkers of cardiac dysfunction in community-acquired pneumonia. (December 2016) - Biteker, F.S.; Başaran, Ö.; Doğan, V.; Çaylak, S. Dirgen; Yıldırım, B.; Sözen, H.
Abstract: The aim of this study was to determine the prognostic role of echocardiography and compare with admission N-terminal proB-type natriuretic peptide (NT-proBNP) levels in adult patients with community-acquired pneumonia (CAP). Consecutive adult patients hospitalized with CAP were prospectively enrolled and followed-up until hospital discharge or death. Echocardiography was performed within the first 48 hours. Complicated hospitalization (CH) was defined as intensive care unit admission, need for mechanical ventilation or in-hospital mortality. This study was registered withClinicalTrials.gov, numberNCT02441855 . A total of 15 CH (13.5%) occurred among 111 patients with CAP. CAP patients with a CH compared with those without CH had significantly higher NT-proBNP values (1267.4±1146.1 vs. 305.6±545.7 pg/mL, p <0.001) and troponin I (23.8±24.3 vs. 10.3±6.3 ng/mL, p 0.02) but had lower left ventricle ejection fraction (52.7±8.7 vs. 60.5±6.7%, p <0.001) and tricuspid annular plane systolic excursion (TAPSE), which is a measure of right ventricular systolic function (17.1±4.4 vs. 21.8±4 mm; p 0.001). Patients with elevation of NT-proBNP and decreased TAPSE at presentation had a significantly higher probability of CH (60%) than patients with either elevated NT-proBNP or decreased TAPSE (40%). Patients with neither elevated NT-proBNP nor decreased TAPSE had a 0% probability of CH. This is the first study to demonstrate that decreased right ventricular systolic function is associated with increased rates of adverse events in patients with CAP.